EFFECT OF MORINGA (Moringa oleifera) LEAF EXTRACT ON IN VITRO INHIBITION OF Candida albicans BIOFILM - Herastuti Sulistyani; Siti Sulastri; Dewi Agustina; Quroti A'yun (Dentino: Jurnal Kedokteran Gigi, 2024)
Background: Oral candidiasis is an opportunistic infection in the oral cavity. This infection is caused by the fungus Candida albicans. The most important virulent attribute of this fungus is its ability to form biofilms, which can adhere to mucosa, epithelial lining, organs, prostheses or dentures. The formed biofilm is resistant to antifungal drugs. Objectives: The purpose of this study was to determine the effect of Moringa (Moringa oleifera) leaf extract on the inhibition of Candida albicans biofilm formation in vitro. Methods: This type of research is experimental study using post tests with control group design. Fungus used in this study was Candida albicans ATCC 10231. Determination of minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) were conducted by microdilution method. Inhibition test of C. albicans biofilm formation was carried out using the polystyrene microplate assay method. Concentration of extracts used in this study were 12.5%, 6.25%, 3.13% and 1.57%. Inhibitory activity of biofilm was measured using a crystal violet (CV) assay. Results: The results showed that MIC of Moringa leaf extract against the fungus C. albicans was at a concentration of 6.25%. Moringa leaf extract starting at a concentration of 3.13% already has had ability to inhibit formation of C. albicans biofilm. Conclusion:  It can be concluded that Moringa leaf extract can inhibit formation of Candida albicans biofilm, so it can be developed as an alternative herbal ingredient to prevent oral candidiasis.EFFECT OF MORINGA (Moringa oleifera) LEAF EXTRACT ON IN VITRO INHIBITION OF Candida albicans BIOFILM